Menimbang Wacana Formalisasi Hukum Pidana Islam di Indonesia - Faisal Faisal (AHKAM : Jurnal Ilmu Syariah, 2012)
Abstract: The Possibility of an Islamic Criminal Law Formalization Discourse in Indonesia. In the discourse of law, criminal law is often viewed as a cruel and barbarian law. This view is based on an assumption that although the application of criminal law aims to restore social balance, it is undeniable that the application of the criminal contains elements of retaliation against the perpetrators of crime. This is reinforced by the severe punishment-oriented model of criminal deprivation of liberty in the form of imprisonment that dominates almost all penal systems of the nations of the world, including Indonesia. This paper proves that the Islamic criminal law legislation in the formalization of the State legislation has a positive contribution in a framework to enrich and bring together a form of awareness of the commitments of the nation and the state.Keywords: law, crime, Islam, formalization, IndonesiaAbstrak: Menimbang Wacana Formalisasi Hukum Pidana Islam di Indonesia. Dalam diskursus ilmu hukum, hukum pidana seringkali dipandang sebagai hukum barbarian yang kejam. Pandangan ini didasarkan pada sebuah asumsi bahwa meskipun penerapan pidana bertujuan untuk memulihkan keseimbangan sosial yang rusak, namun tidak dapat dimungkiri bahwa dalam penerapan pidananya terkandung unsur pembalasan terhadap pelaku kejahatan. Hal ini diperkuat dengan masih massifnya model pemidanaan yang berorientasi pada pidana perampasan kemerdekaan berupa penjara yang mendominasi hampir seluruh sistem pemidanaan negara- negara dunia, termasuk Indonesia. Tulisan ini membuktikan bahwa legislasi hukum pidana Islam ke dalam formalisasi perundang-undangan Negara memiliki kontribusi positif dalam rangka memperkaya sekaligus merekatkan kembali sebagai bentuk penyadaran terhadap komitmen dalam berbangsa dan bernegara.Kata Kunci: hukum, pidana, Islam, formalisasi, IndonesiaDOI: 10.15408/ajis.v12i1.978